Implementacion de indicadores turisticos para evaluar el desarrollo economico en la parroquia chacras, canton Arenillas. - Inga Jaya, Mirka Paulette; Huiracocha Marquina, Maria Cristina (Machala : Universidad Técnica de Machala, 2024)
Due to the lack of economic development in the Chacras parish, Arenillas canton, it is proposed to implement tourism indicators to evaluate the economy. The problem of this integrative project is the lack of evaluation of the economic development caused in this territory, through this integrative project it is proposed to make tourism indicators based on the economy, that is to say, it is intended to make a significant growth in the local tourism market to improve the tourism demand of the sector. It is important to carry out an inquiry to know better the site to be studied, this will be done through the use of data collection instruments among them are: interview and survey because in this way it will be known to real criteria on the current economic situation of the place. Therefore, the projection of this degree work seeks to diversify the economic development and that in turn are suitable for all people in the community regardless of age or any disability, resulting in a number of job openings since, by generating sources of income through tourism, we are laying the foundations for sustainable development and a higher quality of life.
A causa de la ausencia del desarrollo económico en la parroquia Chacras cantón Arenillas, se propone implementar indicadores turísticos para evaluar la economía. La problemática de este proyecto integrador es la carencia de evaluación del desarrollo económico causado en dicho territorio, mediante este proyecto integrador se propone efectuar indicadores turísticos basados en la economía, es decir se pretende realizar un crecimiento significativo en el mercado turístico local para mejorar la demanda turística del sector. Es importante que se realice una indagación para conocer mejor el sitio a estudiar, esto se hará mediante uso de instrumentos de recolección de datos entre ellos son: entrevista y encuesta ya que de esta forma se conocerá a criterio real sobre la actual situación económica del lugar. Por ello la proyección de este trabajo de titulación busca diversificar el desarrollo económico y que a su vez sean aptas para todas las personas de la comunidad sin importar la edad o ninguna discapacidad, dando como resultado una serie de ofertas de trabajo ya que, al generar las fuentes de ingresos a través del turismo, estamos asentando las bases para un desarrollo sostenible y una mayor calidad de vida.
Keywords: DESARROLLO; TURISMO; ECONOMIA; SOSTENIBILIDAD